Diagnóstico comunitario de salud del Barrio Solamar Alto, septiembre-diciembre de 2013 - Terán Albán, Vanessa Johanna (2017)
The present study titled "COMMUNITY DIAGNOSIS OF HEALTH DISTRICT SOLAMAR ALTO, SEPTEMBER - DECEMBER 2013" is framed in the macro-project entitled NURSING PARTICIPATION MODEL OF COMPREHENSIVE HEALTH CARE - MAIS HOSPITAL UNIVERSITY MOTUPE SEPTEMBER-DECEMBER OF 2013, which seeks to contribute to the social development of the town, bringing with statistical data that will enable them to basic health teams Motupe University Hospital, develop strategies for maintaining and improving the health of individuals, families and communities, from a biopsychosocial, multidisciplinary and intercultural approach. This study is descriptive as facts and characteristics related to population and environment is detailed, the instrument for data collection was the family record compiled by the MSP to which I add a container primer necessary information all this being annexed for examination and thus obtain the district's own results. The Quarter is distributed Solamar Alto 33 families and 127 inhabitants. The age group 20 to 64 years together with the dominant male in the population. His education is maintained at a basic level. The occupation of the inhabitants is based on agriculture and household chores. In 33 families there consumption of unsafe water, poor sewage and garbage disposal, and hence poverty poor housing conditions, unemployment or informal employment of the household head and overcrowding. Regarding the epidemiological profile Hypertension is the chronic degenerative prevalent in the population followed Diabetes pathology and a person with visual disabilities are also identified and over with physical disabilities. Research bibliography and appendices which involves the development of it is supported. Keywords: Community Health diagnosis Neighborhood “Solamar Alto” and results.